COMMUNICATION APPROACH FOR AGRICULTURAL TECHNOLOGY TRANSFER IN VARIOUS AGRO-ECOSYSTEM ZONES: A Case Study in South Sumatra Province - Sulaiman, Fawzia (Indonesian Agency for Agricultural Research and Development - MOA, 2002)
An effective communication and dissemination of research results should be based on the natural resource endowment in each agro-ecosystem and the socio-economic background of the prospective clientele. The objective of this study was to examine several forms of communication approaches for disseminating agricultural technology and information. This study was based on a baseline survey conducted in four agroecosystems of South Sumatra Province, i.e. tidal swamp, swamp, dry lowland, and irrigated lowland. Results indicated that the social economic condition and natural resource endowment of farmers in the swamp agro-ecosystem zone (AEZ) of Ogan Komering Ilir is suitable for fishery development instead of food crop agribusiness. However, farmers in the swamp AEZ need technologies that reduce their workload in land cultivation and weeding activities. Further, as field extension workers (FEWs) were considered as the source of agricultural information by most farmers, the involvement of FEWs in agricultural research and technology assessment will increase the effectiveness of the innovation transfer, especially in the tidal swamp and irrigated lowland AEZs. In the four AEZs, the FEWs and farmer group leader can be used as an effective channel to convey agricultural technology and information in South Sumatra Province.